Rubem Braga : crônica e censura no Estado Novo (1938-1939) - Vergara, Anelize [UNESP] (2014)
Rubem Braga’s recognition in the literary world was due to his role as a chronicler, genre to which he was devoted entirely for more than sixty years. He was regarded by experts on the subject, to be responsible for providing the chronicle a unique character, according to Antonio Candido, the “first one to raise the level of chronicle to the highest literary category.” Early in his career of chronicler, collaborated in journals that formed the largest conglomerate of media at the time, the Assis Chateaubriand Diários Associados. However, after a disagreement with Chatô, the chronicler left the conglomerate in 1935, and went on to work in various newspapers in a short period of time, which led him to be called Gypsy by his friend Carlos Drummond. It is significant that most of these publications were in opposition to Vargas, the integralismo and the Catholic Church stance shared by Braga who often resorted to pseudonyms to publish. This research aims to study the chronicles published by Rubem Braga in the early years of its formation as a writer and journalist, in an environment that has not been systematically analyzed. This time coincides with the Estado Novo (1937-1945) and the intensification of institutionalized censorship by the Department of Press and Propaganda (1939). For this purpose, it comes to analyze the texts published between 1938 and 1939 in three different journals and that had simultaneous collaboration of the chronicler, Diretrizes (1938-1944) and Revista Acadêmica (1933-1948), both leftist publications and also the newspaper O Imparcial (1935-1942), aligned to the Estado Novo political project. The aim is to analyze what were the main issues and problems raised by the chronicler, as well as map his intellectual and political positioning on the early years of the newly ...